Pendampingan Penyusunan Delapan Standar Nasional Pendidikan di Satuan PAUD - Mutoharoh, Mutoharoh; Haorah, Haorah; Safiah, Safiah (Civiliza Publishing, 2025)
Early childhood education (ECE) has a crucial role in shaping the foundation of optimal child development. One effort to improve the quality of ECE is to fulfill the eight national education standards (NES). This study uses a descriptive qualitative method with a participatory approach to deeply understand how ECE principals understand and fulfill the eight NES comprehensively. The results of the assistance show positive developments, including an increased understanding of the eight NES, the ability to prepare documents related to the eight NES, and good cooperation between the ECE unit assistance team. This assistance has proven effective in providing the support needed by ECE units to fulfill the eight NES, which in turn improves the quality of early childhood education